Situation Report: Baltic Area, 13 July 1988 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Party First Secretary Replaced by Native Estonian / by Toomas Ilves Massive Demonstrations / by Toomas Ilves Vote to Restore Estonian Flag and Degree Estonian as Official Language / by Toomas Ilves Radical Resolutions Adopted by Meeting of Official and Unofficial Youth Groups / by Toomas Ilves Cultural Leaders Call for Greater National Sovereignty / by Dzintra Bungs The Latvian Communist Party Leadership's Platform / by Dzintra Bungs New Group for Latvian Independence Formed / by Dzintra Bungs People's Front Planned / by Dzintra Bungs Massive Rally in Vilnius / by Saulius Girnius Lithuanian and Estonian Economists Jointly Discuss Proposals for Autonomy / by Saulius Girnius Lithuanian Bishop Named Cardinal / by Saulius Girnius Debate oh History Heads UP / by Kestutis Girnius